Decreased expression of hsa_circ_0001895 in human gastric cancer and its clinical significances. Issue 4 (April 2017) - Shao, Yongfu; Chen, Linbo; Lu, Rongdan; Zhang, Xinjun; Xiao, Bingxiu; Ye, Guoliang; Guo, Junming
Circular RNAs are a special class of endogenous RNAs characterized by jointing 3′ and 5′ ends together via exon or intron circularization. Recent studies found that circular RNAs are involved in the development of some human diseases. However, little is known about their roles in human gastric cancer. In this study, we chose hsa_circ_0001895 as a targeted circRNA to investigate its clinical significances in gastric cancer patients. Hsa_circ_0001895 expression levels in five gastric cancer cell lines and 257 specimens of tissues were measured by real-time quantitative reverse transcription polymerase chain reaction. Then, the potential relationship between hsa_circ_0001895 expression levels and patients' clinicopathological factors was investigated. A receiver operating characteristic curve was constructed for evaluating the diagnostic value of hsa_circ_0001895. Hsa_circ_0001895 expression levels in five detected gastric cancer cell lines (AGS, BGC-823, HGC-27, MGC-803, and SGC-7901) were all significantly downregulated than those in normal gastric epithelial GES-1 cells. Besides, compared with healthy control tissues, it was downregulated not only in 69.8% (67/96) gastric cancer tissues but also in gastric precancerous lesions. Moreover, hsa_circ_0001895 expression levels were significantly correlated with cell differentiation, Borrmann type, and tissue carcino-embryonic antigen expression. Our results suggested that hsa_circ_0001895 may play crucial roles during gastric cancerogenesis and is a potential biomarker for clinical prognosis prediction.